PENGGUNAAN MASALAH DALAM PEMBELAJARAN SUBJEK USUL FIQH: SATU KAJIAN DI UNIVERSITI SAINS ISLAM MALAYSIA - Mohd Subri, Irwan (Jurnal Syariah, 2019)
This study explores the students of Faculty Syariah and Law, Islamic Science University of Malaysia’s perception on the application of teaching methodology for the subject of Usul Fiqh. This method refers to the application of "problem" which has been presented to the students and they were asked to discuss it based on al-Quran, Sunnah, methodology of U!iUl Fiqh and Qawiiid Fiqh. This method will be able to build confident, skills and the students’ capabilities in providing proof and reason on any issue in order to facilitate themselves to become bright future generations who will continue the works of previous mujtahidin. This research is not only intended to get the students’ perception on this teaching methodology but in fact it is done in order to get their response and it is indeed suggested that this method should be implemented in every subject of Islamic studies. The research findings found that the respondents showed positive impact on the learning methodology based on "problematic based learning" (PBL). The result of the research also shows that the application of PBL is able to assist the students to develop their thinking skills to be more creative and critical.